Morphological characteristics of p75 neurotrophin receptor‐positive cells define a new type of glial cell in the rat dorsal root ganglia. Issue 12 (6th March 2019) - Koike, Taro; Tanaka, Susumu; Hirahara, Yukie; Oe, Souichi; Kurokawa, Kiyoshi; Maeda, Mitsuyo; Suga, Mitsuo; Kataoka, Yosky; Yamada, Hisao
Abstract: In the dorsal root ganglia (DRG), two types of glial cells (Schwann cells and satellite glial cells) have been identified based on cell morphology and expression of specific markers. In the present study, we observed unknown glial cells that were positive for p75 neurotrophin receptor (p75NTR), and therefore were immunohistochemically and ultrastructurally characterized for the first time. These cells exhibited stronger immunoreactivity against an anti‐p75NTR antibody than the DRG neurons (hereafter referred to as p75NTR++ cells). Moreover, these cells covered the glial cells surrounding proximal process of the large‐diameter DRG neurons. The proximal process is called "dendro‐axon." The p75NTR++ cells were predominantly distributed where the first myelinating Schwann cells appear. The p75NTR++ cells were also positive for the pan‐glial cell markers S100, nestin, and Sox10, but negative for fibroblast and macrophage markers. Moreover, they were negative for a satellite glial cell marker, inwardly rectifying potassium channel Kir4.1, as well as a nonmyelinating Schwann cell marker, glial fibrillary acidic protein. In addition, their morphological features were distinct from those of the myelinating Schwann cells. To investigate the three‐dimensional ultrastructure of the p75NTR++ cells, we used array tomography combined with correlative light and electron microscopic observation. Three‐dimensional ultrastructural observation revealed that the p75NTR++ cells loosely covered glial cells around the dendro‐axons with highly ramified processes. Glial cells with these morphological features have not been reported before, indicating that the p75NTR++ glial cells are a new glial cell type in the DRG. Our results will give new insights into cell–cell relationships. Abstract : We immunohistochemically and ultrastructurally characterized nonneuronal p75NTR‐positive cells in the dorsal root ganglia for the first time. These cells were positive for pan‐glial cell markers, but their morphological features were distinct from already known glial cells. These morphological results indicate that the p75NTR‐positive glial cells are a new glial cell type.